An Analysis of SBM ITB Library Service Quality a Case Study of the Undergraduate Students Perception and Expectation - Lestari, Ayu Gema; Yudoko, Gatot (Journal of Business and Management, 2016)
Abstract- the main theme of this research is service quality analysis and focus on SBM-ITB library. The purposes of this research are to measure the undergraduate studentsâ€™ perception and expectation of the SBM library services and to propose future improvement using the service quality model (SEVQUAL) and the library service quality (LibQUAL). The questionnaire consists of five major dimensions with a total of 26 variables. They include Tangible dimension (7 variables), Responsiveness dimension (6 variables), Assurance dimension (4 variables), Reliability dimension (5 variables), and Empathy dimension (4 dimensions). Each variable measure perception and expectation with a 7-point Likert Scale. Sampling plan used disproportionate stratified random sampling for 400 students, consisting 100 students for the undergraduate students Batch 2016, 100 students for Batch 2017, and 200 students for Batch 2018. The number of returned questionnaires that can be processed is 233 or 58.2% response rate. Data collected were processed through normality testing using Kolmogorov-Smirnov test, construct validity testing using Pearson correlation coefficient, relaibility testing using Cronbach alpha reliability coefficient, and gap calculation and analysis. All data do not follow normal distribution. All dimension passed the item-to-total Spearman correlation tests. All dimensions have Cronbach alpha coefficient of at least 0.8. All variables have negative gap values. Based on these gaps, future improvement alternatives are proposed.Â Keywords: library service quality, SERVQUAL, LibQUAL, perception, expectation, improvementÂ